2020
DOI: 10.1177/0194599820951150
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Evaluation of a Virtual Elective in Otolaryngology in the Time of COVID‐19

Abstract: Objective To develop and evaluate a virtual otolaryngology medical student elective created during the COVID-19 crisis with the intention of teaching the basic tenets of otolaryngology and increasing exposure to the specialty. Study Design Cross-sectional survey. Setting Emory University School of Medicine. Methods A 1-week virtual otolaryngology curriculum was offered to third- and fourth-year medical students that centered on the American Academy of Otolaryngology–Head and Neck Surgery Foundation’s handbook … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 5 publications
1
30
0
4
Order By: Relevance
“…Studies of didactic-based virtual electives show high student satisfaction as well as significant improvement in medical student performance in post-versus pre-tests on specialty-specific material. 10 , 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of didactic-based virtual electives show high student satisfaction as well as significant improvement in medical student performance in post-versus pre-tests on specialty-specific material. 10 , 11 …”
Section: Discussionmentioning
confidence: 99%
“…For surgical specialties, these virtual curricula have included learning tools such as targeted readings, case-based discussions, simulated or real patient interactions, and instructional surgical videos. 9 , 10 , 11 , 12 , 13 However, literature evaluating the effectiveness of these interventions is limited, and few studies have addressed the significant problem of lack of student access to the operating room (OR) for interactive learning. One study described a virtual surgical subinternship that included simulated surgical skills workshops, 13 and another presented a case report of live-streaming from the OR for medical student education, 14 but neither have yet evaluated the educational value of these virtual experiences from student or faculty perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Such innovations have included national consortia to deliver high-quality faculty lectures, real-time streaming of surgeries, opening access to student attendance at virtual tumor boards and other didactics, interactive discussions with faculty and residents, telesimulation, self-paced curricula, and virtual electives. 12,19,[21][22][23][24] Our program demonstrates how virtual spaces can provide infrastructure for near-peer mentorship that accomplishes objectives of didactic teaching, facilitate resident-student networking, and enables applicants to meet one another, all goals of traditional visiting subinternships built into accreditation standards for both medical students and residents. 4,5 The transition to residency represents a unique opportunity to provide these types of programs, which may strengthen the student experience both during and after the COVID-19 pandemic.…”
Section: "What I Found Most Valuable Was the Opportunity To Meet Currmentioning
confidence: 99%
“…9 Some strategies that have been described to overcome some of the barriers faced by limited face-to-face contact include the creation of virtual electives and surgical skills workshops, online lecture series, mentorship programs, and initiatives targeted to increase diversity, equity and inclusion for under-represented applicants. [12][13][14][15][16][17][18] In our study, we found that providing large group-sessions ensured equal access to information provided about the program and was necessary to maintain fairness during the CaRMS process. We suggest including current residents of all levels of training and former graduates of the program to speak about their experiences as this provides listeners with a diverse experiences and a direct representation of their careers as future urology trainees and alumni.…”
Section: Discussionmentioning
confidence: 73%